Preliminary Study On Latent Membrane Protein-1 (LMP-1) And Bcl-2 Associated X (BAX) In Exosomes Of Patients With Nasopharingeal Cancer In NTB Provincial Hospital - Angrayany Sapar, Puput; Kadriyan, Hamsu; Yudhanto, Didit (Rifa'Institute, 2021)
Nasopharyngeal cancer is one of the most common types of cancer in Indonesia, especially head and neck cancer. One of the etiology of this cancer is infection with Epstein-Barr virus. Early diagnosis is difficult to establish because the early signs and symptoms of nasopharyngeal carcinoma are not specific. Examination of latent membrane protein-1 (LMP1) oncogene expression and BCL2-associated X (BAX) gene expression proved to be useful in the identification of nasopharyngeal cancer. LMP1 oncogene is an oncogene that functions as a tumor necrosis factor receptor (TNFR), so that apoptosis does not occur and promotes invasion and metastasis. The BAX gene is a pro-apoptotic gene that inhibits cancer development, but its regulation will be downregulated by LMP1 because LMP can protect B-cells from apoptosis.